Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Low temperature hydrogenation of tetralin over supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Shirai, Masayuki (Applied Catalysis A-General, 2006)
Hydrogenation of tetralin was studied over supported rhodium catalysts in supercritical carbon dioxide solvent at 333 K. The results were compared with those in an organic solvent and under neat conditions. Higher cis-decalin yield was obtained in supercritical carbon dioxide solvent than under non-supercritical conditions. It was observed that higher hydrogen concentration at the surface in supercritical carbon dioxide solvent led to fast direct hydrogenation of tetralin to cis-decalin; the flipping of the intermediate, octalin, to give trans-decalin could be prevented. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cis-decalin; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide; supported rhodium catalysts; tetralin

Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.

Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.

Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Efficient synthesis of fused 1,2,3-triazolo-delta-lactams using huisgen [3+2] dipolar cycloaddition ``click-chemistry'' in water - Kumar, Indresh; Rode, Chandrashekhar V. (Chemistry Letters, 2007)
A general approach for the quick synthesis of various 1,2,3-triazolo-delta-lactams has been described, which involves the Huisgen [3 + 2] dipolar cycloaddition of azides derived from different amino acids with dimethyl acetylenedicarboxylate in water followed by cyclization.

Phosphotungstic acid as an efficient solid catalyst for intramolecular rearrangement of benzyl phenyl ether to 2-benzyl phenol - Bhure, Mahesh H.; Rode, Chandrashekhar V.; Chikate, Rajeev C.; Patwardhan, Neeraj; Patil, Shraddha (Catalysis Communications, 2007)
An heteropoly acid (phosphotungstic acid, PTA) was found to be a promising solid acid catalyst as an alternative to the conventional stoichiometric reagents for the rearrangement of benzyl phenyl ether giving 2-benzyl phenol as a major product and 4-benzyl phenol and dibenzylated phenols as side products. Catalyst was recovered from the reaction mixture and reused again without loss of activity. Based on the observed product distribution for various substrates a plausible catalytic reaction pathway has also been proposed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzyl phenyl ether; Intramolecular rearrangement; Phosphotungstic acid

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol

Catalytic hydrogenation of 2-butyne-1,4-diol: activity, selectivity and kinetics studies - Rode, Chandrashekhar V. (Journal of the Japan Petroleum Institute, 2008)
The reaction pathway for hydrogenation of 2-butyne-1,4-diol involves parallel and consecutive isomerization as well as hydrogenation reactions forming other side products along with cis-2-butene-1,4-diol and butane-1,4-diol. Hence, achieving the highest selectivity to butene- and/or butanediol is critical from industrial point of view. Hydrogenation of butynediol is also of fundamental significance, due to its adsorption characteristics leading to the formation of active species and their role in determining the product distribution. Studies on designing various catalyst systems including colloidal as well supported palladium nanoparticles for the hydrogenation of butynediol, role of additives, catalyst pretreatment, kinetic studies carried out in our group has been presented in this review. Interestingly, almost complete selectivity to the intermediate olefinic diol was achieved with 1% Pd/CaCO3-NH3 catalyst system. This could be due to the competitive adsorption of ammonia on the palladium surface along with the substrate 2-butyne-1,4-diol. Studies on catalyst pretreatment and kinetics using palladium catalyst have also been presented here. Nanostructure palladium both colloidal as well as supported catalysts showed a very high catalytic activity (10-40 times more) in the hydrogenation 2-butyne-1,4-diol to cis-2-butene-1,4-diol compared with the corresponding conventional Pd catalysts. For platinum based catalysts, formation of side products was completely eliminated in the hydrogenation of butyne diol. The increase in the basic strength of alkali metal doped Pt catalysts measured by CO2-TPD, led to the increase in electron density of Pt hence, faster desorption and higher selectivity to butenediol. In the case of continuous hydrogenation, the selectivity pattern was completely different from that found in the case of batch slurry reactor and by varying the contact time, the selectivity to both butene- and butanediols could be varied over a wide range of conditions.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; catalyst pretreatment; nano palladium catalyst; Selective hydrogenation

Enhancement of glycerol conversion to acetol in high-temperature liquid water by high-pressure carbon dioxide - Yamaguchi, Aritomo; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2008)
Dehydration of glycerol to acetol proceeded in high-temperature liquid water at 573 K in a batch reactor. The acetol formation rate increased with an addition of high-pressure carbon dioxide.

Facile and highly selective deprotection of tert-butyldimethyl silyl ethers using sulfated SnO2 as a solid catalyst - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Rode, Chandrashekhar V. (Synthetic Communications, 2008)
Highly selective deprotection of tert-butyldimethylsilyl ethers at room temperature has been described using sulfated SnO2 as an efficient solid catalyst.
Keywords: deprotection; sulfated SnO2; TBDMS ethers

Highly active nanostructured Co3O4 catalyst with tunable selectivity for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Vijayanand, Subramanian; Potdar, Hari S.; Joy, Pattayil Alias; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chemistry Letters, 2008)
This is a first report of highly efficient heterogeneous nanostructured Co3O4 catalyst (6-8 nm) having high surface area (95 m(2)/g) developed for selective liquid phase air oxidation of p-cresol under atmospheric pressure conditions.

Iron-nickel bimetallic nanoparticles for reductive degradation of azo dye orange G in aqueous solution - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Applied Catalysis B-Environmental, 2008)
The degradation of Orange G, a monoazo dye, in aqueous solutions was investigated using Fe-Ni bimetallic nanoparticles. Transmission electron microscopy (TEM) of as-synthesized nanoparticles showed the presence of spherical particles having a size of 20-40 nm. X-ray photoelectron spectroscopy (XPS) did not detect the presence of nickel on the nanoparticle surface, which suggested a uniform distribution of both metals inside the particle core. Batch experiments with a minimum nanocatalyst loading of 3 g/L showed complete dye degradation after 10 min of reaction time. The degradation efficiency was linearly dependent on the initial dye concentration, pH of the solution and total Fe-Ni catalyst concentration. The efficiency increased with increasing Fe-Ni concentration and decreasing pH of the solution, but decreased with an increase in the dye concentration. The degradation rate followed first order reaction kinetics with respect to the dye concentration. High performance liquid chromatography-mass spectrometry (HPLC-MS) analysis of the degradation products revealed that the degradation mechanism proceeds through a reductive cleavage of the azo linkage resulting in the formation of aniline and surface-adsorbed naphthol amine derivatives. The latter are subsequently hydroxylated through an oxidative process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Azo Dye; Degradation; iron; Nanoparticles; Nickel

Phosphotungstic acid on silica with modified acid sites as a solid catalyst for selective cleavage of tert-butyldimethylsilyl ethers - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Catalysis Communications, 2008)
The strength and nature of acid sites of bulk phosphotungstic acid could be modified after dispersing it on silica support which was characterized by XRD, ammonia TPD and (31)P MAS NMR techniques. This solid acid catalyst was found to be highly selective for the cleavage of tert-butyldimethylsilyl ethers at room temperature. The catalyst was easily recovered by filtration and could be reused for several times without loss of any activity giving a TON of 9.5 x 10(5). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Catalytic cleavage; reaction pathway; solid acid; tert-butyldimethylsilyl ethers; XRD

Activity and selectivity behavior of 1,2-epoxyethylbenzne hydrogenation in carbon dioxide solvent - Rode, Chandrashekhar V.; Hiyoshi, Norihito; Mine, Eiichi; Shirai, Masayuki (Industrial & Engineering Chemistry Research, 2009)
Catalytic hydrogenation of 1,2-epoxyethylbenzene to 2-phenylethanol over charcoal-supported noble metal in carbon dioxide was studied, and the results were compared with those in heptane and methanol. Charcoal-supported palladium and platinum (Pd/C and Pt/C) catalysts were active metal species for the hydrogenation in solvents. The order of activities over palladium and platinum was heptane < carbon dioxide < methanol; however, the formation of dehydroxylated byproduct was suppressed in carbon dioxide solvent. Negative carbon dioxide pressure effect was observed over the Pd/C and Pt/C catalysts in the carbon dioxide solvent.

Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Heterogeneous cobalt-saponite catalyst for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2009)
Heterogeneous Co-saponite was found to be an efficient catalyst for the liquid phase oxidation of p-cresol under mild conditions. Divalent cobalt tons were found to be in both the tetrahedral and octahedral positions of the saponite clay. Studies on the effect of reaction parameters showed that the rate of reaction increased with increase in Co loading from 5 to 13% and then remained constant up to 30% of Co loading, while the rate of oxidation showed a first-order dependence on the partial pressure of oxygen up to 300 kPa. Results of oxidation experiments over Co-saponite, in an Inert atmosphere, and the XPS studies Suggest Mars-van Krevelen pathway operating, which involves lattice oxygen of Co-saponite in the liquid phase oxidation of p-cresol.

Liquid phase oxidation of p-cresol over cobalt saponite - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Topics in Catalysis, 2009)
Liquid phase oxidation of p-cresol was carried out over a Co-saponite catalyst in a temperature and pressure range of 333-393 K and 20-827 kPa, respectively in n-propanol. Co-saponites with varying cobalt content (5-30%) were prepared and screened among which 13% Co-saponite gave the highest conversion of 92% of p-cresol with 92% selectivity to p-hydroxybenzaldehyde without formation of any non-oxidation products.
Keywords: Co-saponite; Liquid phase oxidation; p-Cresol; p-Hydroxybenzaldehyde; XPS

Phase behavior of hydrogenation of 2-tert-butylphenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent - Hiyoshi, Norihito; Masuda, Yoshio; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of Chemical and Engineering Data, 2009)
Catalytic hydrogenation of 2-tert-butyl phenol over a charcoal-supported rhodium catalyst in carbon dioxide solvent at 313 K was studied in a batch reactor. To elucidate the effect of carbon dioxide pressure on the initial rate of reaction, the phase behavior of the ternary (2-tert-butylphenol-carbon dioxide-hydrogen) system was separately observed with a view cell, and the calculations of vapor-liquid equilibrium and compositions in the vapor and liquid phases inside the reactor were carried out using the Peng-Robinson equation of state. The hydrogenation behavior in the carbon dioxide solvent is discussed based on the phase behavior of the ternary system.

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-methylphenol) using Sn/Si-MCM-41 catalysts - Garade, Ajit C.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (Chemistry Letters, 2010)
Sn/Si-MCM-41 has exhibited an excellent catalytic activity [70% product yield with 88% selectivity to 2,2'-methylenebis(4-methylphenol)] for the selective hydroxyalkylation of p-cresol. At equal level of Sn loading, Sn/Si-MCM-41 prepared by direct hydrothermal synthesis showed higher activity than Sn-impregnated Si-MCM-41 catalyst.

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Pd-functionalized carbon nanotubes for selective hydrogenation of 2-butyne-1,4-diol - Nadgeri, Jayprakash M.; Garade, Ajit C.; Tambe, Romana A.; Gokhale, Suresh P.; Rode, Chandrashekhar V. (Advanced Science Letters, 2010)
Multiwalled carbon nanotubes were prepared by thermal decomposition method followed by acid treatment and Pd-functionalization with PdCl2 by wet impregnation method. The Pd functionlized carbon nanotubes catalyst was characterized by BET, FT-IR, Raman, XRD, EDX, ICP-OES, SEM and TEM and was evaluated for its activity for hydrogenation of 2-butyne-1,4-diol. It showed higher selectivity (93%) to 2-butene-1,4-diol than Pd supported on commercial carbon (70% selectivity to 2-butene-1,4-diol) for complete conversion of 2-butyne-1,4-diol. The catalyst also exhibited excellent stability as evidenced by the three catalyst recycle experiments.

Proline catalyzed direct diastereoselective 6-enolexo aldolization: toward the synthesis of the imino sugar DNJ - Kumar, Indresh; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
A L-proline catalyzed direct diastereoselective 6-enolexo aldolization reaction of differentiating dialdehydes derived from tartaric acid is presented This organocatalytic approach provides high levels of synselectivity (dr > 10 1) with the stereocontrolled C-C bond formation between C4 and C5 intramolecularly which can serve to synthesize Imino-sugar skeleton quickly (C) 2010 Elsevier Ltd All rights reserved

Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Synthesis of hybrid 1,2,3-triazolo-delta-lactams/lactones using Huisgen [3+2] cycloaddition `click-chemistry' in water - Kumar, Indresh; Rana, Sravendra; Cho, Jae Whan; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
The synthesis of a new class of hybrid 1,2,3-triazozlo-delta-lactams/lactones has been achieved using the Huisgen [3+2] dipolar cycloaddition `click-chemistry' reaction of various organic azides with an activated alkyne in water, followed by cyclization. (C) 2010 Elsevier Ltd. All rights reserved.

Control of competing hydrogenation of phenylhydroxylamine to aniline in a single-step hydrogenation of nitrobenzene to p-aminophenol - Nadgeri, Jayprakash M.; Biradar, Narayan S.; Patil, Priyanka B.; Jadkar, Sachin T.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2011)
Two steps involving catalytic hydrogenation of nitrobenzene to phenylhydroxylamine (PHA) in acid medium and its rearrangement to p-aminophenol (PAP) were studied separately in a batch reactor, using a well-characterized 3% Pt/C catalyst. The first step of hydrogenation of nitrobenzene to PHA could be carried out at 303 K and a H(2) pressure of 0.69 MPa with complete conversion of nitrobenzene, while the achieved selectivity to PHA was higher than 90% with some formation of aniline, even at lower temperature. The second step of PHA rearrangement to PAP could be achieved under a hydrogen atmosphere at elevated temperature of 353 K to give a maximum selectivity to PAP of 74%.

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Liquid phase oxidation of p-vanillyl alcohol over synthetic Co-saponite catalyst - Garade, Ajit C.; Biradar, Narayan S.; Joshi, S. M.; Kshirsagar, V. S.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Applied Clay Science, 2011)
Effect of cobalt loading on porosity of synthetic Co-saponite catalysts and on the air oxidation of p-vanillyl alcohol was studied by varying Co content in the range of 5% to 30% using in situ precipitation method. The pore size increased from 1.29 to 3.69 nm indicating a transition from micro to meso porosity, with increase in Co loading from 5% to 30%. The distribution ratio of Co(3)O(4)/CoO phases as estimated from TPR studies, also increased from 0.84 to 1.67 with increase in Co loading from 5% to 13% and remained almost constant (1.7) with further increase in Co loading up to 30%. The highest activity (conversion 55%) and selectivity of 99% to p-vanillin obtained for 13% Co-saponite in p-vanillyl alcohol oxidation was due to the highest distribution ratios of Co(3)O(4)/CoO phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Co-saponite; Cobalt oxide phase ratio; p-Vanillin; p-Vanillyl alcohol oxidation; Porosity transition; Temperature programmed reduction

Reply to the comments of vicente et al. on ``liquid phase oxidation of p-vanillyl alcohol over synthetic co-saponite catalyst'' applied clay science (2010), doi:10.1016/j.clay.2010.10.026 - Rode, Chandrashekhar V.; Garade, Ajit C.; Biradar, Narayan S.; Kshirsagar, V. S. (Applied Clay Science, 2011)

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Continuous dehydration and hydrogenolysis of glycerol over non-chromium copper catalyst: laboratory-scale process studies - Mane, Rasika B.; Rode, Chandrashekhar V. (Organic Process Research & Development, 2012)
A non-chromium Cu:Al catalyst was developed for glycerol dehydration under N-2 atmosphere to acetol and hydrogenolysis to 1,2-propanediol (1,2-PDO). Among the various copper-based catalysts screened in this work, Cu:Al-1 catalyst showed the highest activity and acetol selectivity in water medium, whereas transfer hydrogenation in 2-propanol as the reaction medium led to the formation of 1,2-PDO (10-38%). The same catalyst was also found to catalyze the direct hydrogenolysis of glycerol to 1,2-PDO. Time on stream activity (TOS) of our Cu:Al-1 catalyst for both continuous dehydration and hydrogenolysis of glycerol was found to be 400 h with an average glycerol conversion of 90% and 65%, respectively. Maximum acetol selectivity was 55% while 1,2-PDO selectivity was 91% in dehydration and hydrogenolysis reactions separately. Effects of various reaction conditions on conversion, selectivity, and global rates of the two processes were also investigated.

Cu-ZrO2 nanocomposite catalyst for selective hydrogenation of levulinic acid and its ester to gamma-valerolactone - Hengne, Amol M.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Several copper based catalysts were prepared, characterized and evaluated for the hydrogenation of levulinic acid and its methyl ester. Among these, nanocomposites of Cu-ZrO2 and Cu-Al2O3 quantitatively catalyzed the hydrogenation of levulinic acid and its methyl ester to give 90-100% selectivity to gamma-valerolactone in methanol and water respectively. Both the Cu-ZrO2 and Cu-Al2O3 nanocomposites were prepared by the co-precipitation method using mixed precursors under controlled conditions. XRD results showed that the main active phase of the reduced Cu-ZrO2 catalyst was metallic copper and particle size was found to be of 10-14 nm by HRTEM. The active metal leaching was at a maximum for the Cu-Al2O3 catalyst in a water medium due to the formation of a copper-carboxylate complex that was blue in colour. Surprisingly, copper leaching was completely suppressed in the case of the Cu-ZrO2 catalyst in methanol in spite of the substrate loading was increased from 5 to 20% w/w. The excellent recyclability of the Cu-ZrO2 catalyst with complete LA conversion and > 90% GVL selectivity makes it a sustainable process having a commercial potential.

Kinetic analysis of 4-isopropylphenol hydrogenation over activated carbon-supported rhodium catalysts in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Green Chemistry, 2012)
Hydrogenation behavior of 4-isopropylphenol to 4-isopropylcyclohexanol over activated carbon-supported rhodium catalysts in supercritical carbon dioxide (scCO(2)) at 313 K was studied in a batch reactor and the results were compared with those in 2-propanol. Higher yields of cis-4-isopropylcyclohexanol were obtained in scCO(2) than in 2-propanol, and the formation of a byproduct, isopropylcyclohexane, was suppressed in scCO(2). The catalyst modification with hydrochloric or phosphoric acid enhanced the yield of cis-4-isopropylcyclohexanol in both scCO(2) and 2-propanol solvents. Kinetic analyses of the reaction profiles revealed higher reaction rates in scCO(2) than those in 2-propanol for the 4-isopropylcyclohexanol formation both by the direct hydrogenation of 4-isopropylphenol and by the consecutive hydrogenation of 4-isopropylcyclohexanone, and also revealed that the addition of hydrochloric acid increased the consecutive hydrogenation rate of 4-isopropylcyclohexanone to cis-4-isopropylcyclohexanol, which reduced the total reaction time needed for the complete hydrogenation of 4-isopropylphenol to 4-isopropylcyclohexanol.

MCM-41 supported phosphotungstic acid for the hydroxyalkylation of phenol to phenolphthalein - Jha, Ajay; Garade, Ajit C.; Mirajkar, Subhash P.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
A novel application of phosphotungstic acid, H3PW12O40 (PWA) supported on MCM-41 molecular sieve as a solid acid catalyst has been demonstrated for the synthesis of phenolphthalein by hydroxyalkylation of phenol and phthalic anhydride. PWA/MCM-41 (20%) showed the highest activity as compared to that of parent PWA and MCM-41 individually, due to the excellent dispersion of PWA on MCM-41 leading to the redistribution of Bronsted and Lewis acid sites on MCM-41. The effect of PWA loading on phthalic anhydride conversion and phenolphthalein selectivity was also studied. All these prepared catalysts were characterized by XRD, N-2 adsorption-desorption isotherm, pyridine-FTIR, and NH3-TPD. The effect of various reaction parameters, namely, mole ratios, catalyst concentration, temperature, reaction time, and percentage of PWA present in the catalysts on conversion and selectivity of products has been also investigated. The utility of 20% PWA/MCM-41 catalyst was established by its efficient activity for hydroxyalkylation of phenol and p-cresol with formaldehyde to the corresponding dihydroxydiarylmethane products.

Reply to comment on ``Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles'', by C. Noubactep - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2012)

Selectivity tuning options in hydrogenation of m-chloronitrobenzene to m-chloroaniline over mono- and bimetallic supported Pt catalysts - Mane, Rasika B.; Potdar, Aparna S.; Nadgeri, Jayprakash M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
Supported monometallic (Pt, Ni,) and bimetallic (Ni-Pt) catalysts were prepared for the selective liquid phase hydrogenation of m-chlronitrobenzene to m-chloroaniline (m-CAN). It was found that the use of sodium carbonate as an additive substantially reduced the extent of dehydrohalogenation in the case of monometallic, 1% Pt/C catalyst, to give the highest selectivity of 96% to m-CAN. Ni-Pt bimetallic catalyst although showed almost complete selectivity (>99%) to m-chloroaniline; its activity was several fold lower than that of 1% Pt/C Na2CO3 system. However, compared with Ni monometallic catalyst, bimetallic Ni-Pt showed higher activity and selectivity due to the presence of electron rich surface metallic Pt stabilized by Ni having lower ionization potential compared with Pt.

Simultaneous glycerol dehydration and in situ hydrogenolysis over Cu-Al oxide under an inert atmosphere - Mane, Rasika B.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Among various catalysts screened, the Cu-Al oxide catalyst, prepared by a co-precipitation method, exhibited excellent activity for simultaneous glycerol dehydration and its hydrogenolysis without external hydrogen. Detailed characterization by XRD, XPS, HR-TEM, TPR, etc., showed evidence of Cu2+ in the form of CuO and CuAl2O4, along with Cu-0 and Cu1+ species, which are responsible for their multifunctional roles in glycerol APR, dehydration and hydrogenolysis reactions under inert conditions. This catalyst also presented consistent activity for a duration of 400 h for autogeneous hydrogenolysis of refined glycerol with 36% selectivity to 1,2-propanediol (1,2-PDO). Manipulating the temperature and feed flow rate conditions, meant that the selectivity to acetol and 1,2-PDO could be tailored as desired. Substantial enhancement in 1,2-PDO selectivity (75%) was achieved for an aqueous bio-glycerol feed over the same catalyst for 50 h of testing.

Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Active sites in modified copper catalysts for selective liquid phase dehydration of aqueous glycerol to acetol - Mane, Rasika B.; Yamaguchi, Aritomo; Malawadkar, Atul V.; Shirai, Masayuki; Rode, Chandrashekhar V. (RSC Advances, 2013)
We report here the influence of oxides of various metals viz. Ba, Mg, Zr, Zn, Al, and Cr in modified copper catalysts, on the formation of different copper species and acid sites responsible for dehydration of aqueous glycerol to acetol. These catalysts were prepared by a co-precipitation method, among which the catalysts having higher acid strength and predominant Bronsted acidity (Cu-Mg, Cu-Zr and Cu-Al) gave the highest acetol selectivity (76-92%), while the catalysts with lower acidity such as Cu-Zn showed very poor (25%) selectivity to acetol in spite of the highest conversion of 68%. Nevertheless, catalysts exhibiting higher activity and acetol selectivity also showed the presence of metallic Cu confirmed by XRD and XANES-EXAFS characterization. Based on these results, two different catalytic pathways have been proposed highlighting the role of Lewis and Bronsted acidity along with the metal sites in individual steps of glycerol dehydration reaction.

Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid

Heterogeneous Co3O4 catalyst for selective oxidation of aqueous veratryl alcohol using molecular oxygen - Mate, Vivek R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Catalysis Communications, 2013)
Nano-structured, spinel Co3O4 catalyst was developed for the aqueous phase oxidation of veratryl alcohol, which showed the highest conversion of 85% with 96% selectivity to veratryl aldehyde. The co-existence of Co3+ and Co2+ species in the octahedral and tetrahedral positions respectively, was confirmed by XPS, cyclic voltammogram, TPR and TPO characterization. The rod-like morphology of Co3O4 catalyst was confirmed by HRTEM. The effects of various reaction parameters namely, catalyst concentration, temperature and partial oxygen pressure on conversion and selectivity patterns were also studied for the oxidation of veratryl alcohol. This catalyst also showed an excellent stability as evidenced by successful reusability for three times. (C) 2012 Published by Elsevier B.V.
Keywords: Co3O4; Cyclic voltammogram; Liquid phase oxidation; Molecular oxygen; Veratryl alcohol; XPS

Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Highly selective liquid-phase aerobic oxidation of vanillyl alcohol to vanillin on cobalt oxide (Co3O4) nanoparticles - Jha, Ajay; Rode, Chandrashekhar V. (New Journal of Chemistry, 2013)
Spinel Co3O4 nanoparticles prepared by solution phase method having particle size in the range of 12-20 nm exhibited excellent activity for the liquid-phase aerobic oxidation of vanillyl alcohol with 80% conversion and 98% selectivity to vanillin. Our catalyst could be reused three times without appreciable loss in activity. The catalytic activity of the Co3O4 nanoparticles was found to be similar to its homogenous precursor (cobalt acetate) and greater than the commercial Co3O4 oxide. The detailed characterization results of morphology, size and structure of the prepared Co3O4 nanoparticles obtained by XRD, FT-IR, H-2-TPR, HR-TEM and cyclic voltammetry technique were used to understand the roles of various Co species in directing the selectivity towards vanillin.

Magnetically separable single-site Ti-Fe3O4@MCM-41 catalyst for selective epoxidation of olefins - Jha, Ajay; Patil, Chetana R.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2013)
Magnetically separable Ti-Fe3O4@MCM-41 (Ti-MS) catalysts were prepared by postgrafting Ti with varying loading on mesoporous silica containing dispersed magnetite. The hexagonal structure of Ti-MS catalysts with a periodicity in the pores and a highly ordered hexagonal matrix was established by X-ray diffraction and transmission electron microscopy, while diffuse reflectance UV showed the isolated tetrahedral Ti species coordinated with O2-. From the Fourier transform infrared studies, the extent of Ti-O-Si linkage was found to increase with increase in Ti-loading from 1 to 5 wt %beyond which (10%), the intensity of Ti-O-Si band decreased due to the polymerization of the Ti on the silica surface. Silanol groups on the surface of silica interact with the precursor Ti((OPr)-Pr-i)(4) to give site isolated tetrahedral Ti-species responsible for complete selectivity to the epoxide in the epoxidation of cyclooctene. The magnetic property facilitated easy recovery of the catalyst for its successful eight recycles showing its stability under reaction conditions.

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Solvothermal synthesis of mesoporous manganese oxide with enhanced catalytic activity for veratryl alcohol oxidation - Jha, Ajay; Chandole, Tejansh; Pandya, Rajan; Roh, Hyun-Seog; Rode, Chandrashekhar V. (RSC Advances, 2014)
Catalyst activities of manganese and cobalt oxides prepared by solvothermal and co-precipitation methods were studied for veratryl alcohol oxidation. Manganese oxides showed higher activity performance than that of cobalt oxides irrespective of the method of preparation. The solvothermal method yielded mesoporous manganese oxide without using any template giving mixed phases of monoclinic Mn5O8 and hausmannite Mn3O4. The mesoporous manganese oxide exhibited excellent activity for liquid phase aerobic oxidation of veratryl alcohol under base free conditions, with 90% conversion and almost complete selectivity towards veratraldehyde. The detailed characterization results on morphology, size and composition of the prepared mesoporous manganese oxide obtained by XRD, XPS, H-2-TPR, N-2 adsorption-desorption isotherms, FESEM and HR-TEM techniques were used to understand the role of morphological and structural features in enhancement of the observed catalytic activity.

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.

Tailoring the product dstribution with batch and continuous process options in catalytic hydrogenation of furfural - Biradar, Narayan S.; Hengne, Amol A.; Birajdar, Shobha N.; Swami, Rameshwar; Rode, Chandrashekhar V. (Organic Process Research & Development, 2014)
Various noble metal catalysts were screened in a batch operation for a furfural (FFR) single-step decarbonylation and hydrogenation reaction to obtain THF in high selectivity. Among these, the 3% Pd/C showed complete FFR conversion with a total of 80% selectivity to ring hydrogenated products including tetrahydrofuran (THF). The order of activity exhibited by other noble metals was Pt/C > Re/C > Ru/C. Although Pt/C exhibited the highest activity, its decarbonylation and ring hydrogenation ability were the least (24%) with a major product selectivity of 66% to furfuryl alcohol (FAL). Similarly, the Cu catalyst gave almost complete selectivity to FAL. In a continuous operation (23 g catalyst bed), the 3% Pd/C catalyst showed higher selectivity of >40% compared to THF alone with complete FFR conversion and on-stream activity of similar to 100 h. The reaction pathway elucidated from some control experiments revealed that the decarbonylation of FFR to furan over the Pd/C catalyst is a prerequisite for THF formation.

Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Highly efficient triphenyl(3-sulfopropyl)phosphonium functionalized phosphotungstic acid on silica as a solid acid catalyst for selective mono-allylation of acetals - Kamble, Sumit B.; Shinde, Suhas H.; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2015)
Silica supported phosphotungstic acid functionalized with triphenyl(3-sulfopropyl)phosphonium (PW-Si/TPSP) was developed as a solid acid catalyst for C-C bond formation via Hosomi-Sakurai allylation of acetals. Functionalization of PW as well as its binding to silica was confirmed by solid state P-31-NMR and Si-29-NMR, respectively. Among the various catalysts prepared, the 30% PW loaded (30PW-Si/TPSP) catalyst gave an excellent yield of homoallyl ethers (HAEs) via selective mono-allylation of acetals with allyltrimethylsilane. A plausible reaction pathway has also been proposed in which the strong Bronsted acid sites of 30PW-Si/TPSP play an important role in activating the acetals to form the corresponding oxonium cations. The versatility of our catalyst was demonstrated for the allylation of a wide variety of acetals while its stability was established in five successful recycling runs.

Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.

Mesoporous NiCu-CeO2 oxide catalysts for high-temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Jang, Won-Jun; Rode, Chandrashekhar V.; Roh, Hyun-Seog (RSC Advances, 2015)
Mesoporous NiCu-CeO2 oxide catalysts were synthesized by using the evaporation-induced self-assembly method applied to the high-temperature, water-gas shift reaction (HT-WGS) between 350 to 550 degrees C. Nickel and copper loadings on mesoporous ceria were tailored to achieve high activity and selectivity by suppressing methane formation in HT-WGS. Among the prepared catalysts, NiCu(1 : 4)-CeO2 exhibited the highest selectivity to CO2 and H-2 with 85% CO conversion at a very high GHSV of 83 665 h(-1). The higher activity of the catalysts was due to the mesoporous architecture, which provides more accessible active sites for the WGS reaction. Powder X-ray diffraction (XRD), small angle X-ray scattering (SAXS), N-2-adsorption/desorption isotherm, high-resolution transmission electron microscopy (HR-TEM), and H-2-temperature-programmed reduction (TPR) techniques were used to understand the role of mesoporosity and bimetallic composition of various NiCu-CeO2 oxides in enhancing catalytic activity for HT-WGS.

Reduced graphene oxide composite with oxidizable manganese/cobalt mixed oxide for p-cresol oxidation by using molecular oxygen - Jha, Ajay; Patil, Sagar H.; Solanki, Bhanu P.; Ribeiro, Ana P. C.; Castro, Carlos A. N.; Patil, Kashinath R.; Coronas, Alberto; Rode, Chandrashekhar V. (ChemPlusChem, 2015)
A composite of graphene oxide (GO) with mixed oxide (MnCo) was prepared by using a solvothermal method. During the synthesis, both the reduction of GO and growth of metal oxides took place simultaneously. The as-prepared composite material was highly selective for the liquid-phase oxidation of p-cresol to form p-hydroxybenzaldehyde in 71% yield within 1h. The composite material was characterised by SEM, X-ray photoelectron spectroscopy, high-resolution TEM and cyclic voltammetry (CV). A CV study revealed that the increase in the redox potential of the mixed oxide after being supported on GO, led to its higher activity of the catalyst for the oxidation reaction. The stability of the catalyst under the reaction conditions was studied by its successful reuse in three cycles.
Keywords: cyclic voltammetry; graphene; Oxidation; supported catalysts; transition metals

Cascade synthesis of 2-cyanoacrylamides through deacetalization and/or knoevenagelcondensation followed by selective monohydration of acetals and aldehydes over solid acidferrites - Kamble, Sumit B.; Rode, Chandrashekhar V. (Chemcatchem, 2016)
A new protocol of cascade synthesis for biologically active 2-cyanoacrylamides (1) was developed. The reaction proceeds over a novel magnetically retrievable solid-acid composite of iron oxide, poly(vinylpyrrolidone) and phosphotungstic acid (Fe3O4/PVP-PWA) in AcOH-H2O medium under reflux conditions. This transformation is facilitated through single-site Bronsted acid catalyzed cascade reactions involving deacetalization and/or Knoevenagel condensation followed by selective monohydration of nitriles starting from acetals (5) and aldehydes (2) with malononitrile (3). A series of aldehydes, dimethyl and diethyl acetals, along with some heterocyclic aldehydes were successfully transformed to 2-cyanoacrylamides with >95% yields. TEM images confirmed the coating of the PVP over nanosized Fe3O4. Stereoselective monohydration of 2-benzylidenemalononitriles (4) to E isomers was demonstrated by NOESY experiments. The catalyst could be efficiently recycled seven times on employment of both acetals and aldehydes as substrates, as a result of its magnetic nature.

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Highly selective direct azidation of alcohols over a heterogeneous povidone-phosphotungstic solid acid catalyst - Kamble, Sumit; More, Sagar; Rode, Chandrashekhar V. (New Journal of Chemistry, 2016)
A simple protocol for the selective azidation of alcohols is developed using a solid acid hybrid of a povidone and phosphotungstic acid (PVP-PWA) using azidotrimethylsilane as an azide source at room temperature. In a broad substrate scope, various activated as well as unactivated benzylic and diphenyl alcohols were treated smoothly with TMS-N-3 to selectively produce only azide products with excellent yields in a very short reaction time of 2 h. FT-IR confirmed the stability of the catalyst with retention of the Keggins structure after the reaction. Recycling experiments demonstrated the reusability of the PVP PWA (3:1) several times without losing its original activity.

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.

Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.

Catalytic ozonation of clofibric acid over copper-based catalysts: in situ ATR-IR studies - Sable, Shailesh S.; Ghute, P. P.; Fakhrnasova, D.; Mane, R. B.; Rode, Chandrashekhar V.; Medina, F.; Contreras, S. (Applied Catalysis B-Environmental, 2017)
The current study describes the catalytic ozonation of clofibric acid (CFA) under ambient conditions using copper oxide catalysts synthesized by different methods. The objective of this study is to provide novel catalysts and reaction mechanism for the degradation of emerging pharmaceutical compounds in aqueous solution. Among the various Cu catalysts screened in this study, the Cut-Ali oxide catalyst showed an excellent activity and stability in the degradation and mineralization of CFA. In situ attenuated total reflection IR (ATR-IR) spectroscopy was used to examine the interaction of ozone with the active sites of the catalyst in presence of water and to investigate the possible catalytic mechanism. The presence of Lewis acid sites in the Cut-Ali catalyst increased the amount of chemisorbed water enhancing stronger interaction of ozone to form surface activated species, resulting in higher catalytic activity. The results obtained from in-situ ATR-IR study indicate that surface hydroxyl groups and Lewis acid sites are responsible for promoting the generation of hydroxyl radicals (OHS) from aqueous ozone. (C) 2017 Elsevier B.V. All rights reserved.

Efficient palladium catalyzed Mizoroki-Heck cross-coupling in water - Jadhav, Sanjay N.; Rode, Chandrashekhar V. (Green Chemistry, 2017)
The homogeneous Pd-catalysed Mizoroki-Heck coupling reaction was successfully performed in water in the absence of any additives under aerobic conditions. The various key reaction parameters that affect the yield of the desired cross-coupling product were optimized. The Pd(PPh3)(4)/Et3N/H2O/98 degrees C catalyst system was found to be highly active (TOF = 12 to 14 h(-1)) towards achieving excellent yield of the Mizoroki-Heck coupling products for a wide range of electron-withdrawing as well as electron-donating aryl bromides and chlorides in the shortest reaction time. Pd(PPh3) 4 catalyst deactivation during the Mizoroki-Heck coupling reaction was investigated and to evolve a strategy for achieving ten times Pd-metal recyclability without appreciable loss of its activity. Thus, the proposed mechanism provides access to a variety of olefins in aqueous medium, making this protocol eco-friendly.

Heterogeneously catalyzed domino synthesis of 3-indolylquinones involving direct oxidative C-C coupling of hydroquinones and indoles - Kamble, Sumit B.; Vyas, Praneet P.; Jayaram, Radha V.; Rode, Chandrashekhar V. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-5/acsomega.7b00201/20170523/images/medium/ao-2017-00201p_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">A domino synthesis of 3-indolylquinones was achieved successfully via direct oxidative C–C coupling of hydroquinones with indoles over Ag2O and Fe3O4/povidone–phosphotungstic acid (PVP–PWA) catalysts using H2O2 in tetrahydrofuran at room temperature. Ag2O catalyzed the in situ oxidation of hydroquinone and 3-indolylhydroquinone intermediates, whereas ferrite solid acid, Fe3O4/PVP–PWA, with a 1:4:1 ratio of Fe3O4, PVP, and PWA, catalyzed the activation of quinones. The efficiency of this catalytic domino approach was established by a broad scope of substrates involving a variety of hydroquinones and quinones to give high yields (81–97%) of 3-indolylquinones. Fe3O4/PVP–PWA was separated magnetically, whereas simple filtration could separate Ag2O, both of which could be recycled several times without losing their activities.
Keywords: Carbonyl compounds (organic); Electron microscopy; Fourier-transform spectroscopy; Redox reaction

Influence of carbon based supports on selectivity behavior of diols and propanol in Ru catalyzed glycerol hydrogenolysis - Mane, Rasika B.; Patil, S.; Shirai, Masayuki; Rayalu, Sadhana S.; Rode, Chandrashekhar V. (Applied Catalysis B: Environmental, 2017)
Activated carbon (AC) and three graphite materials were studied as supports for Ru catalyzed glycerol hydrogenolysis to propanediols and 1-propanol. Structural characteristics of AC and graphite materials were found to greatly affect the reducibility and particle size of supported Ru and hence, the activity and product distribution in glycerol hydrogenolysis. XRD of graphite materials showed distinctly (002) plane having highly organized layered structure and the peak intensity decreased in the order of Ru/KS150 > Ru/HSAG100 > Ru/KS6 due to decrease in the graphite sheet thickness. In Raman, the intense D band in HSAG100 compared to that in KS6 and KS150 samples indicated its highly amorphous nature or mixed carbon hybridization. Glycerol conversion for Ru on AC was higher than that on graphite and among different graphites, it showed a descending activity order of Ru/KS6 > Ru/HSAG100 > Ru/KS150. The product distribution for AC and HSAG100 supported Ru was similar, giving 1-propanol (45%) alongwith 1,2-propanediol (1,2-PDO) (37%) and 1,3-propanediol (1,3-PDO) (9–11%). For graphite supports, availability of Ru although bigger in size (4–5 nm), would be higher on the surface than in case of AC which formed deep hydrogenolysis products like 1-, 2- propanol, ethanol etc.
Keywords: activated carbon; Amorphous carbon; catalysis; Glycerol; Glycerol conversions; Glycerol hydrogenolysis; graphite composites; Graphite supports; Hydrogenolysis; Hydrolysis; layered structures; Particle size; Product distributions; Propanediols; Propanol; Selectivity behavior; Structural characteristics; Structural effect; Structural effects

MCM-41-supported phosphotungstic acid-catalyzed cleavage of C-O bond in allyl aryl ethers - Sakate, Sachin S.; Kamble, Sumit B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (New Journal of Chemistry, 2017)
Removal of the protecting allyl group from allyl aryl ethers in the presence of other oxygen protecting groups was successfully achieved using a solid acid supported on the high surface area material MCM-41. The catalyst showed excellent activity in the presence of various electron withdrawing, electron donating, and oxidizable functional groups. The methodology is also very useful for the removal of protecting allyl groups of various natural products such as vanillin, isovanillin, and other oxygen functionalized aldehydes and ketones.

Bifunctional role of Pd/MMT-K 10 catalyst in direct transformation of furfural to 1,2-pentanediol - Date, Nandan S.; Chikate, Rajeev C.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (Catalysis Today, 2018)
The acid functionality of montmorillonite clay K 10 (MMT-K 10) was found to play a key role to give 1,2-pentanediol (1,2-PeDO) in Pd catalysed furfural hydrogenation. Among various Pd loadings on MMT-K 10, 3% Pd/MMT-K 10 catalyst exhibited excellent performance giving almost complete conversion of FFR and the highest selectivity of 66% to 1,2-PeDO. Py-IR of the catalyst evidenced the presence of Brønsted acidity which was responsible in C5-O cleavage of furan ring after the formation of furfuryl alcohol which is the first step intermediate in FFR hydrogenation. At a lower temperature of 140 °C, highest selectivity of 56% was achieved for FAL while increase in temperature to 220 °C, enhanced the selectivity to 1,2-PeDO. Keeping the temperature constant at 220 °C, with increase in H2 pressure from 500 to 750 psig, resulted in decrease in 1,2-PeDO selectivity from 66 to 34% with proportionate increase in THFAL selectivity. Thus as per the requirement, the product selectivities can be tailored by varying the reaction parameters suitably. Several control experiments were also performed the results of which combined with the characterization data allowed to propose a plausible reaction pathway for the formation of 1,2-PeDO.

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.

Integrated production of diesel fuel precursors from carbohydrates and 2-methylfuran over Sn-mont catalyst - Shinde, Suhas H.; Rode, Chandrashekhar V. (ChemistrySelect, 2018)
A TfOH-catalyzed highly efficient synthesis of biologically active (E)-2-cyanoacrylamides and 3-substituted azetidine-2,4-diones has been reported with 64-94% yields under metal-free conditions. The reaction proceeds through sequential Knoevenagel condensation/stereoselective in situ monohydration of nitrile or C-N cyclization protocol in one-pot. The attractive features of this tandem process are moderate reaction conditions, high atom economy, broad substrate scope, gram-scale reaction and ease of operation.

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Single-pot reductive rearrangement of furfural to cyclopentanone over silica-supported Pd catalysts - Date, Nandan S.; Kondawar, Sharda E.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ACS Omega, 2018)
Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO2) showed remarkable results, achieving almost 98% furfural (FFR) conversion with similar to 89% selectivity and 87% yield to cyclopentanone at 165 degrees C and 500 psig H-2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e, cyclopentanone, whereas all of the other supports were found to give ring hydrogenation as well as side chain hydrogenation products due to their parent Bronsted acidity and specific support properties. X-ray diffraction data revealed the presence of different phases of the face-centered cubic lattice of metallic Pd along with lowest crystallite size of 15.6 nm in the case of the silica-supported Pd catalyst. However, Pd particle size was found to be in the range of 5-13 nm with even dispersion over the silica support, confirmed by high-resolution transmission electron microscopy analysis. While studying the effect of reaction parameters, it was observed that lower temperature gave low furfural conversion of 58% with only 51% CPO selectivity.. Similarly, higher H-2 pressure lowered CPO selectivity with subsequent increase in 2-methyl furan and ring hydrogenation product 2-methyl furan and 2-methyl tetrahydrofuran. Thus, as per the requirement, the product selectivity can be tuned by varying the type of support and/or the reaction parameters suitably. With the help of several control experiments and the characterization data, a plausible reaction pathway was proposed for the selective formation of cyclopentanone.

Steering the ester and gamma-valerolactone selectivities in levulinic acid hydrogenation - Kasar, Gayatri B.; Date, Nandan S.; Bhosale, P. N.; Rode, Chandrashekhar V. (Energy Fuels, 2018)
Both alkyl esters and γ-valerolactone (GVL) derived from levulinic acid (LA) have applications as renewable transportation fuel/fuel additives. Non-noble metal cobalt supported on La2O3 catalyst was developed for efficient cascade LA hydrogenation to GVL via esterification. LA hydrogenation in methanol alone yielded methyl levulinate (MeLA) as a major product along with 43% of GVL. Interestingly, hydrogenation in water gave almost complete selectivity to GVL; nevertheless, it was associated with significant metal leaching. Suppression of metal leaching and enhancement in selectivity to GVL could be achieved by a methanol/water (95:5) solvent system. XRD analysis of La2O3-supported catalysts evidenced the characteristic peaks of a mixture of La2O3 and La(OH)3 phases. Basicity, as well as acidity, of the catalyst as determined by CO2 and NH3 TPD was due to these La2O3, Co–La, and La(OH)3 phases which played an important role in directing the product selectivity in levulinic acid hydrogenation. At the low temperature of 160 °C, almost equal selectivities of MeLA (47%) and GVL (43%) were observed, while higher temperature (200 °C) favored further hydrogenation of MeLA to GVL (75%). Similarly, with an increase in reaction time to 9 h, the GVL selectivity achieved was as high as 80%. The selectivity to MeLA and GVL in LA hydrogenation over Co/La2O3 catalyst can be altered by suitably adjusting the reaction conditions.

Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15

Fluorescent carbon-dots thin film for fungal detection and bio-labeling applications - Gaikwad, Aarti; Joshi, Meenal; Patil, Kashinath; Sathaye, Shivaram; Rode, Chandrashekhar V. (ACS Applied Bio Materials, 2019)
The fluorescence properties of CDs, such as high quantum yield, tunability of emission color, and so on, make a strong potential material in various fields. These applications are mainly derived from in situ formation of surface functional groups, high chemical stability, biocompatibility, and easy interaction with substrates, etc. Mostly, the research applications of CDs concentrate on the labeling of biological species, drug delivery, and sensing in consequent biomedical applications. However, the detection of the fungal species/spores present in the environment by using CDs is rarely reported. Herein, we demonstrate CDs-based thin film as a sensor for detection of fungal spores from the environment. The procedure of detection is based on fluorescence, observed in the film of carbon dots deposited on quartz plates by using the Blodgett technique. It is observed that the CDs film shows quenching in the fluorescence intensity by the substrate, namely, fungal spores’ (Aspergillus niger, Penicillium chrysogenum, Alternaria alternata). The effective features of the present detector system are easy fabrication, low cost, high stability, and a green and economical procedure of synthesis. The process of detecting fungal spores even at low concentration from the atmosphere is relatively fast when compared to presently used methods. Finally, real-world feasibility of the sensor film is tested by its successful application for the determination of the presence fungal spores in the environment. Furthermore, CDs have been also successfully applied for the bio-labeling of Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) bacterial systems.

Valorization of oceanic waste biomass: a catalytic perspective - Lucas, Nishita; Athawale, Anjali A.; Rode, Chandrashekhar V. (Chemical Record, 2019)
Efficacious waste utilization is vital in context of sustainability. The past decade has witnessed attempts of usage of land biomass and wastes for various applications, contributing towards a sustainable society. Exploitation of the marine biomass, which does not compete with habitation and food production like land biomass has been largely unnoticed and therefore not being utilized judiciously. Researchers have mainly exploited these resources as functional materials having significant potential applications. However, a catalytic perspective for the valorisation of these polymers arising from oceanic waste widens their scope and ameliorates its use. The objective of the present review is to demonstrate the effectiveness of chitin/chitosan as a catalyst and as a feedstock for deriving important fuels and chemicals. It displays all the reactions heterogeneously catalyzed by them along with the strategic methodology. Their important catalytic organic transformations attempted so far, have also been discussed. The future perspectives are also presented which if inculcated would improve the value addition of the waste, paving a way for greener and imperishable world.

Water-promoted surface basicity in FeO(OH) for the synthesis of pseudoionones (PS) and their analogues - Vernekar, Dnyanesh; Sakate, Sachin S.; Rode, Chandrashekhar V.; Jagadeesan, Dinesh (Journal of Catalysis, 2019)
Use of Iron oxyhydroxide (gamma-FeO(OH)) as a robust catalyst for the synthesis of important intermediates like pseudoionones and their analogues through the C-C bond formation reactions like knoevenagel and aldol condensation is explored. These motifs are the building blocks for the construction of the sesquiterpenes as well as the diterpenes such as retinoic acid, Vitamin A etc. Iron oxyhydroxide (gamma-FeO(OH)) was synthesized and well characterized using XRD, FT-IR, TEM, XPS and adsorption studies to establish the catalytic activity. A thorough investigation on the nature of basic sites and the role of water as a promoter was explored based on dye adsorption, in situ methanol dissociation and CO2 adsorption studies. The catalyst also showed a wide range of substrate scope with active methylene groups involving various functional groups such as cyanides, esters and acetophenones along with its stability and reproducibility. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Bronsted basicity; Iron (III) oxyhydroxide; Knoevenagel condensation; Pseudoionones; Surface hydroxyl groups

Bio-surfactant: a green and environmentally benign reaction medium for ligand-free Pd-catalyzed Mizoroki-Heck cross-coupling reaction in water - Patil, Seema P.; Jadhav, Sanjay N.; Rode, Chandrashekhar V.; Shejwal, Rajendra V.; Kumbhar, Arjun S. (Transition Metal Chemistry, 2020)
A simple and efficient protocol for the ligand-free Mizoroki-Heck coupling reaction of various aryl bromides with different olefins has been reported by using in situ generated PdNPs of size 5-10 nm in aqueous solution of bio-surfactant. The bio-surfactant used in this study is a saponin extract of the seeds of pericarps (pods) of theAcacia concinnaplant. The in situ generated PdNPs have been characterized by various techniques such as HRTEM, EDS and XPS. The influence of various parameters such as the nature and amount of bases, the nature of Pd precatalysts as well as the effect of temperature has been investigated on Mizoroki-Heck coupling reaction. The generated PdNPs significantly coupled the various aryl bromides with different olefins in aqueous extract of the seeds of pericarps (pods) of theAcacia concinnaplant at 100 degrees C. [GRAPHICS] .

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Lignocellulose-derived platform molecules: an introduction - Shinde, Suhas H.; Hengne, Amol; Rode, Chandrashekhar V. (Recent Advances in Development of Platform Chemicals, 2020)
Fossil feedstocks such as crude oil, natural gas, and coal are formed by natural anaerobic decomposition of buried organisms for a period of more than 650 million years. On the other hand, agrobiomass is quick to grow and becomes a renewable source of chemical and fuel production through processing in a biorefinery.
Keywords: Biomass; Biorefinery Cellulose; Lignocellulose Petrofinery; Platform molecules

One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism

Organocatalytic cascade knoevenagel-michael addition reactions: direct synthesis of polysubstituted 2-amino-4H-chromene derivatives - Jadhav, Sanjay N.; Patil, Seema P.; Sahoo, Dipti Prava; Rath, Dharitri; Parida, Kulamani; Rode, Chandrashekhar V. (Catalysis Letters, 2020)
In this report, we documented novel strategy for the synthesis of bioactive polysubstituted 2-amino-4H-chromine derivatives under a heterogeneous Al-MCM-41-LDH@APTES (ALAM) catalysis. A synthetic procedure is developed to prepare Al-MCM-41-LDH@APTES (ALAM) heterogeneous basic catalysts. Mesoporous Al-MCM-41 is functionalized by known grafting chemistry via layered double hydroxide (LDH) nanosheets and (3-aminopropyl)triethoxysilane (APTES) moiety as a basic organocatalyst. The resulting catalysts contain amino group functionality on the external surface as well as inside the layers and the basicity can be tuned by the loading of APTES. The samples were fully characterized by Si-29 and C-13 CP/MAS NMR, infrared absorption spectroscopy, TEM, XPS, EDX, TGA, XRD, CO2-TPD, N-2 adsorption isotherms measurements, and they were successfully examined for the cascade type Knoevenagel-Michael addition reactions. The product yields associated with these substrates were optimized, and key reaction parameters affecting the yields were identified. The present catalytic method is simple and robust for diversity oriented synthesis which proceeds good to excellent yields without generating any hazards waste. The broad substrate scope, excellent functional group compatibility makes this protocol highly useful towards synthesis of polysubstituted alpha-cyanoacrylates, alpha-cyanoacrylonitriles and 2-amino-4H-chromenes with an electron-donating or electron-withdrawing group. We have also successfully established a flow reaction system, gram-scale synthesis as well as catalyst recyclability up to six catalytic cycles without appreciable loss of its activity. Graphic
Keywords: 2-Amino-4H-chromines; Amine functionalized solid catalysts; cascade synthesis; Diversity oriented syntheses (DOS); flow chemistry

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis

Solvent free, environment benign synthesis of 1,4-dihydropyridines and polyhydroquinolines by using heterogeneous Zn/MCM-41 catalyst - Dhengale, Shankar D.; Naik, Vaibhav M.; Kolekar, Govind B.; Rode, Chandrashekhar V.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2021)
Heterogeneous catalysis has been utilized in number of efficient reactions with higher selectivity of the product, more stable, reusable and easy for separation as compared to homogeneous catalysts. Generally, heterogeneous catalysts are prepared by using mesoporous materials, microporous materials, metal oxides and metal organic framework. The mesoporous materials have small particle size and high surface area as compared to the microporous materials. The adsorbent mesoporous materials have highly efficient for the therapeutic applications in chemistry hence it has best as compared to other heterogeneous materials. Herein, we have reported synthesis of 1,4-dihydropyridines and polyhydroquinolines at solvent free and environmental benign condition in the presence of Zn/MCM-41 catalyst. The present protocol gives excellent yield (89-96%) of the product within short reaction time by easy work up procedure and no need of further purification of product. The catalyst was characterized by XRD diffractometer, SEM, EDAX, TGA-DTA, BET surface area analysis and FT-IR Spectroscopy. The synthesized organic compounds were characterized by FT-IR, H-1 NMR, C-13 NMR, LC-MS spectrometry.
Keywords: High activity; High selectivity; mesoporous materials; microporous materials; Reusability of catalyst

Conversion of benzyl phenyl ether to monoaromatics in high-temperature aqueous ethanol solution under high-pressure carbon dioxide conditions - Taniguchi, Kenkichi; Kusumawati, Etty N.; Nanao, Hidetaka; Rode, Chandrashekhar V.; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (New Journal of Chemistry, 2023)
Solvolysis of benzyl phenyl ether (BPE), which is a model compound of lignin ether linkage, was studied in an aqueous ethanol solution, which can be obtained from bioethanol, under high-pressure carbon dioxide conditions. A batch study revealed that BPE solvolysis to monoaromatics (benzyl ethyl ether (BEE), benzyl alcohol (BA), and phenol (Ph)) proceeded in aqueous ethanol solution over 523 K and the addition of high-pressure carbon dioxide enhanced the initial solvolysis rate and suppressed the side reaction (hydrogenolysis to toluene (TL)). The ethanol molar fraction (ethanol-water volume ratio) is the key factor for the solvolysis reaction, and the highest monoaromatic yield of 72.9% (BEE 10.7%, BA 19.3%, Ph 37.9%, and TL 5.1%) was obtained in aqueous ethanol solution (2 cm(3) : 1 cm(3) = water:ethanol) at 598 K for 3 h under a pressure of 18 MPa of carbon dioxide. The solvolysis reaction proceeded continuously to produce monoaromatics with a flow system. A monoaromatic yield of 76.7% (BEE 8.6%, BA 19.7%, Ph 39.6%, and TL 8.9%) was obtained, and the formation rates were 2.7 x 10(-4) mmol min(-1) for BEE, 6.2 x 10(-4) mmol min(-1) for BA, and 12.4 x 10(-4) mmol min(-1) for Ph at 598 K under flowing water (26 mmol min(-1)), ethanol solution (4.1 mmol min(-1)), carbon dioxide (1.2 mmol min(-1)), and BPE (15.6 x 10(-4) mmol min(-1)) under a total pressure of 40 MPa.

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock

Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction

Etherification of biomass-derived glycerol to oxygenated fuel additives using dodecatungstophosphoric-silica-supported catalyst: characterization and kinetic studies - Magar, Subhash B.; Kapoor, Ashish; Jana, Sumit Kumar; Pal, Dan Bahadur; Rode, Chandrashekhar V. (Biomass Conversion and Biorefinery, 2023)
Commercial biodiesel production is becoming popular due to its sustainability and reduced greenhouse gas emissions in comparison to fossil fuels. Biodiesel production involves the co-generation of crude glycerol that is not directly viable. Valorization of glycerol is essential from techno-economic perspective to achieve goals of circular economy. In this study, the glycerol etherification was carried out using tert-butyl alcohol in presence of dodecatungstophosphoric/silica (DTP/SiO2) catalyst for production of tert-butyl glycerol ethers that can be used as fuel additives. A series of DTP/SiO2 catalysts were prepared with various compositions by impregnating heteropoly acids (HPA, H3PW12O40). The product analysis was performed to monitor mono-, di-, and tri-tert-butyl glycerol ethers. The kinetic studies were conducted based on Langmuir-Hinshelwood model. The rate constants were determined from experimental data by regression analysis. The catalysts were characterized by X-ray diffraction, SEM/EDX, and thermogravimetric analysis. Varying DTP loadings resulted in different catalytic activities. Activation energy (38.23 kJ/mol), activation enthalpy (25.94 kJ/mol), activation entropy (-163.8 J/mol/K), and Gibbs free energy of activation (88.67 kJ/mol) were attained for DTP/SiO2 (20%) catalyst that exhibited the best selectivity for di-tert-butyl glycerol ethers.
Keywords: Catalytic; etherification; fuel additives; Hinselwood; Impregnation; kinetics; Langmuir

Novel sulfonic acid functionalized silica supported isonicotinic acid catalyst for conversion of 2-methylfuran to diesel fuel precursors - Tarade, Komal P.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (Catalysis Letters, 2024)
Polyfuranic compounds produced after carbon up-gradation of 2-methylfuran by acid catalyzed C-C bond forming reactions when undergo hydro-deoxygenation produce diesel fuel. Herein, we prepared a simple and novel silica supported sulfonic acid functionalized isonicotinic acid SO3H-INA@SiO2 catalyst by treating isonicotinic acid with chlorosulphonic acid followed by heterogenization on silica. This heterogeneous solid acid catalyst was explored for the solvent free conversion of 2-methylfuran to diesel fuel precursors of C-15 and C-20 units via tandem ring opening followed by condensation sequence. Under optimized reaction conditions, SO3H-INA@SiO2 was able to convert, 2-methylfuran completely into condensation products such as 5,5-bis(5-methylfuran-2-yl)pentan-2-one (1) and 2,4,4-tris(5-methylfuran-2-yl)pentan-1-ol (2) with 19% and 67% yields, respectively. The heterogeneous SO3H-INA@SiO2 catalyst was successfully recycled up to six consecutive runs without loss of its activity. The SO3H-INA@SiO2 catalyst offered superior activity as compared to the commercially available -SO3H functionalized resins. Superior activity of the prepared catalyst could be attributed for its higher acidity, smaller particle size and high surface area. Structure of the prepared catalyst was confirmed by FTIR and solid state NMR. Total acidity of the prepared catalyst was determined by acid-base titration.
Keywords: 2-Methylfuran; Diesel fuel; heterogeneous catalyst; Ionic solid; solid acid

ZrO2 supported Cu nanoparticles for sonogashira and ullmann coupling reactions under palladium-free conditions - Patil, Seema P.; Rajmane, Archana S.; Jadhav, Sanjay N.; Rajmane, Vijaya S.; Rode, Chandrashekhar V.; Kumbhar, Arjun S. (Catalysis Letters, 2024)
Cu nanoparticles supported on ZrO2 (CuNPs@ZrO2) were synthesized using a one-step co-precipitation process, and their application in C-C coupling reactions was investigated. The catalyst was characterized using XRD, XPS, SEM, TEM, and TGA techniques. The prepared catalyst was used for the Sonogashira cross-coupling reactions of aryl bromides with phenyl-acetylene in the presence of K2CO3 in DMF at 110 degrees C, which resulted in substituted alkynes with good to excellent yields. The protocol was also extended for the Ullmann coupling reactions of aryl iodides under similar reaction conditions, yielding the desired products with good to excellent yields without homo-coupling. Interestingly, unlike other copper catalysts, the present catalyst worked under air and did not require an inert atmosphere to prevent alkyne. This catalytic system is versatile, tolerant, and significantly cheaper than the ``traditional'' Pd-catalyzed Sonogashira cross-coupling of terminal alkynes with aryl halides. The catalyst could be reused for five catalytic cycles with no significant change in the product yield. All of these characteristics make our prepared CuNPs@ZrO2 catalyst quite suitable for the gram-scale synthesis of biaryls and alkynes, with a simple workup.{GRAPHIACAL ABSTRACT
Keywords: CuNPs; Recyclability; Sonogashira coupling; Ullmann coupling; ZrO2

pH-Responsive and antimicrobial polymer synthesis in continuous flow and effect of pendant alkylamine on the squaraine dye photocatalyst activity - Patil, Anil M.; Nawghare, Indrajeet S.; Siby, Jesna; Bankar, Priyanka M.; Dastager, Syed G.; Rode, Chandrashekhar V.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (ACS Applied Polymer Materials, 2026)
pH-responsive and antimicrobial polymers were synthesized by photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under blue light (lambda max = 485 nm) using a scalable continuous flow method. The effect of pendant alkylamino groups with different alkyl substituents on methacrylate monomers under blue light is investigated in the absence of a tertiary alkylamine reagent and in the presence of cyanopentanoic acid dithiobenzoate and 4-cyano-4-[(dodecylsulfanylthiocarbonyl) sulfanyl]pentanoic acid as RAFT agents. The rate of polymerization is found to vary with the size of the alkyl chain and with the tertiary, secondary, or quaternary nature of the amino group. The ability of pendant alkylamino groups to transfer electrons to the photocatalyst is shown using cyclic voltammetry and fluorescence quenching experiments; the tendency to suppress dye aggregation is observed using UV-vis spectroscopy; and the rates of polymerization could be correlated with the trend in these results. The mechanism of polymerization is proposed to follow a reductive or oxidative electron transfer pathway depending on the nature of the pendant group. Statistical and diblock copolymers with 2-hydroxyethyl methacrylate are synthesized in batch and continuous flow processes with a comparative study of kinetics in the two methods. The synthesis of high-molecular-weight homopolymer (55,000 g/mol) and statistical copolymer (85,000 g/mol) of N,N-diisopropylaminoethyl methacrylate is shown in continuous flow. The solution self-assembly of diblock copolymers is studied, and the pH-responsive morphology change leading to disassembly is shown. The antimicrobial properties of polymers with a quaternary ammonium pendant group are evaluated. The thermal degradation of statistical copolymers is analyzed.
Keywords: alkylaminoethyl methacrylate; Antimicrobial; continuous flowprocess; PET-RAFT; pH-responsive; self-aggregation